A comprehensive analysis of solitary wave run-up at sloping beaches using an extended experimental dataset. (September 2022) - Casella, Federico; Aristodemo, Francesco; Filianoti, Pasquale
Abstract: In this work, the phenomenon of wave run-up induced by solitary waves in breaking and nonbreaking conditions has been investigated. Despite several studies have been carried out to study this kind of physical process, a robust determination of solitary wave run-up on plane beaches over a wide range of wave conditions and beach slopes is still lacking. In this context, 99 laboratory tests were undertaken in the wave channel of the University of Calabria by adopting three beach slopes and three water depths. The experimental set-up was made up of four wave gauges, a pressure transducer, a velocimeter and an adjustable waterproof ramp to reproduce the plane sloping beach. Using graduated markers along the beach and a video camera, the run-up was deduced. The present experiments cover a range not extensively analyzed in literature, and specifically related to wave run-up comparable or greater than the water depth. The laboratory run-up, velocity and pressure data were validated using the IH-2VOF numerical model. Two different approaches, both for breaking and nonbreaking conditions, were used to obtain semi-analytical formulas for the wave run-up. The first approach is conventional, being based on wave non-linearity and beach slope, while the second is based on the wave energy. Highlights: Laboratory and numerical investigation on solitary wave run-up at sloping. The calculation of the run-up has been performed as a function of the wave amplitude or the wave energy based on the Buckingham theorem. Limits and capabilities of literature formulas have been investigation.